VD_FINDINFO AI 389/08 - 360/2011 vom 18. Juli 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL | 28 al. 1 LAI, 29 al. 1 LAI, 16 LPGA, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 29bis RAI, 88a al. 1 RAI, 88a al. 2 RAI